Investigating the mechanisms of neural-visceral coupling for therapeutic applications - Elliott, Natasha Alicia (2023)
Anxiety and mood disorders are commonly characterised by emotion regulation difficulties. Research suggests meditation practice improves emotion reactivity and well-being by modifying attention regulation. Most meditation practices involve directing attention towards internal sensations, such as the breath. It is thought that attending to internal signals re-calibrates executive function processes, such as how attention is allocated and the number of cognitive resources required to process such information. Studies have shown meditation modifies neural activity in brain regions associated with executive function and enhances relaxed states, indicated by an increase in autonomic vagal tone. However, despite meditation originating several thousand years ago, the interaction between these neural and physiological mechanisms and how they relate to therapeutic effects is yet to be understood. This thesis examines the mechanisms of neural-visceral integration during breath-focused meditation (Su-soku) to facilitate psychopathological knowledge and the development of future therapeutic interventions.